Level of knowledge and learning exposure on cleft lip and palate treatment among undergraduate Universitas Indonesia dental students - Dwi Ariawan; Yudy Ardilla Utomo; Nadya Deva Angriandananti; Mohammad Adhitya Latief; Vera Julia; Lilies Dwi Sulistyani (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Cleft lip and palate are the most common congenital orofacial anomalies. Dental students must have a basic knowledge, understanding, and awareness of comprehensive cleft management. The Faculty of Dentistry Universitas Indonesia undergraduate program uses the problem-based learning (PBL) method to teach dental students about cleft management. Purpose: This study aims to determine the level of knowledge and exposure to learning with the PBL method regarding comprehensive cleft management. Methods: A cross-sectional design was used, and data were collected from 253 dental students using an online questionnaire via Google Forms. Results: Ten preclinical students (8.5%) had a low level of knowledge, 56 (47.5%) had a sufficient level of knowledge, and 52 (44.1%) had a high level of knowledge of comprehensive cleft management. Among the clinical students, 6 (4.4%), 65 (48.1%), and 64 (47.4%) demonstrated low, sufficient, and high levels of knowledge, respectively. Furthermore, most students were content with the lectures on comprehensive cleft management (46.24% satisfied and 20.55% very satisfied) and the supervision received during the lectures (43.48% agreed and 23.71% strongly agreed). Most students believed the lectures on cleft management could be applied when they graduate as dentists. The Chi-square test showed no significant relationship between learning exposure and the student’s knowledge level. Conclusion: Most Faculty of Dentistry Universitas Indonesia students who had learned about cleft lip and palate using the PBL method had sufficient knowledge about comprehensive cleft management. However, no significant relationship was observed between learning exposure and knowledge level.